Regulation of Notch Signaling by the Heterogeneous Nuclear Ribonucleoprotein Hrp48 and Deltex in Drosophila melanogaster. Issue 2 (1st June 2017) - Dutta, Debdeep; Paul, Maimuna Sali; Singh, Ankita; Mutsuddi, Mousumi; Mukherjee, Ashim
Abstract: Notch signaling is an evolutionarily conserved pathway that is found to be involved in a number of cellular events throughout development. The deployment of the Notch signaling pathway in numerous cellular contexts is possible due to its regulation at multiple levels. In an effort to identify the novel components integrated into the molecular circuitry affecting Notch signaling, we carried out a protein–protein interaction screen based on the identification of cellular protein complexes using co-immunoprecipitation followed by mass-spectrometry. We identified Hrp48, a heterogeneous nuclear ribonucleoprotein in Drosophila, as a novel interacting partner of Deltex (Dx), a cytoplasmic modulator of Notch signaling. Immunocytochemical analysis revealed that Dx and Hrp48 colocalize in cytoplasmic vesicles. The dx mutant also showed strong genetic interactions with hrp48 mutant alleles. The coexpression of Dx and Hrp48 resulted in the depletion of cytoplasmic Notch in larval wing imaginal discs and downregulation of Notch targets cut and wingless . Previously, it has been shown that Sex-lethal (Sxl), on binding with Notch mRNA, negatively regulates Notch signaling. The overexpression of Hrp48 was found to inhibit Sxl expression and consequently rescued Notch signaling activity. In the present study, we observed that Dx together with Hrp48 can regulate Notch signaling in an Sxl-independent manner. In addition, Dx and Hrp48 displayed a synergistic effect on caspase-mediated cell death. Our results suggest that Dx and Hrp48 together negatively regulate Notch signaling in Drosophila melanogaster .